Disparitas Putusan Hibah: Studi Analisis di Pengadilan Malang, Pengadilan Agama Tinggi Surabaya dan Mahkamah Agung - Kamarusdiana Kamarusdiana; Zakiyah Salsabila (JURNAL INDO-ISLAMIKA, 2019)
The term “grant” (hibah) in the Law Book of Civil Code (KUH Perdata) has been regulated in the Article from 1666 to that of 1693, while the Compilation of Islamic Law (KHI) regulates the grant mentioned in the Article from 210 to that of 214. The subject matter of grant in the Religious Courts and the High Court of Religion in Indonesia is the first and an appeal that the religious court was not authorized to decide on the case for the cancellation of the grant certificate, but at the appellate level. Next, the judges overturn the first and appeal and decision. Finally, the decision on the Cassation level has given rise to the principle of Legal Certainty, Legal Justice and the Principle of Expediency.